HUBUNGAN VOLUME DARAH PADA SAAT MENSTRUASI DENGAN KEJADIAN ANEMIA PADA MAHASISWA AKADEMI KEBIDANAN INTERNASIONAL PEKANBARU TAHUN 2014 - Berliana Irianti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Young women are still many who suffer from anemia. One cause of anemia in adolescent girls are menstruating. Some women menstruate every month and the duration between 2-7 days. The purpose of this study was to examine the association of menstruation with anemia in international midwifery academy students pekanbaru 2014. This study is a quantitative research with cross sectional approach. The number of sample of 64 students. sampling technique using accidental sampling. Measurement of hemoglobin using the method of Sahli. Analysis of data using univariate and bivariate analysis. Known from the 64 students who menstruate most normal menstruating as many as 40 people. And students who menstruate most anemic as many as 57 people. Selanjutnya in the analysis using chi-square test and concluded that there was association between menstruation with anemia in Pekanbaru Internasional Midwifery Academy students in 2014. Internasional Midwifery Academy students are expected to increase knowledge about anemia and hemoglobin level is checked regularly.